Modelos para evaluar la complejidad de los proyectos de construcción de infraestructura - Durón-González, Flavio Roberto; Rivas-Tovar, Luis Arturo; Cárdenas-Tapia, Magali (Ingeniería, 2022)
Context: Infrastructure enables the satisfaction of the population’s needs and contributes significantly to the economic development of countries and regions. However, Flyvbjerg points out that the success rate of construction projects is estimated at only 25 % and, particularly in megaprojects, it is 8 successful projects per 1000. On the other hand, several studies point out that complexity has negative effects on project performance, so it is of interest to evaluate such complexity and to sensibilize project managers to anticipate its negative effects. Method: Trough a literature review, four relevant complexity models were identified. Using a heuristic analysis technique, they were analyzed in three aspects: 1) factors contributing to project complexity, 2) types of projects and their specific complexity factors and, 3) techniques and tools used in the models to study project complexity. Results: The most comprehensive model is Lessard, Sakhrani & Miller’s HoPC. By considering the project’s life cycle, on Bosch-Rekveldt’s TOE framework, seven complementary complexity aspects were identified: project architecture, financial complexity, governance, the validation process of project stages, project management maturity, cultural aspects, and the regulatory framework. Conclusions: Recent studies highlight that environment and externalities are increasingly relevant in assessing the complexity of infrastructure construction projects. Projects exhibit aspects of complexity depending on their internal components and on the specific context in which they are undertaken, so the development of subject-specific models is recommended. Project complexity has been addressed mainly from Project Management and Systems Dynamics approaches, however, for the study of the diversity, interdependence, and dynamics among the complexity factors future research from the Complex Systems approach is needed.